4/9 nhân x + 14/9 nhân x = 13,2 : 0,01
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-1\right)\left(x-3\right)< 0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x-1>0\\x-3< 0\end{matrix}\right.\) hoặc \(\left\{{}\begin{matrix}x-1< 0\\x-3>0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x>1\\x< 3\end{matrix}\right.\) hoặc \(\left\{{}\begin{matrix}x< 1\\x>3\end{matrix}\right.\)( vô lí )
\(\Leftrightarrow1< x< 3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
480 ⋮ a ⇔ a ϵ Ư(480)
Ư(480) = {1; 2; 3;4;5; 6;8;10;12;15;16;20;24;30;32;40;60;96;160;480}
180 ⋮ x và 2 < x < 5
x ϵ Ư(180)
Ư(180) = {1;2;3;4;5;....180}
vì 2<x<5 ⇔ x = 3; 4
![](https://rs.olm.vn/images/avt/0.png?1311)
2n + 1⋮3n + 1
=> 3 (2n + 1)⋮3n + 1
=> 6n + 3⋮3n + 1
=> 2 (3n + 1) + 1⋮ 3n + 1
Vì 2(3n + 1) + 1⋮3n + 1 mà 2(3n + 1)⋮3n + 1 nên 1⋮3n + 1
=> 3n + 1ϵ Ư(1) = {1;-1}
=> n = 0
Vậy n = 0
![](https://rs.olm.vn/images/avt/0.png?1311)
{132 - [ 115 - ( 16- 8) ] : 2} .5
= {132 -[ 115 - 8] :2} .5
= {132 - 107:2} .5
= \(\dfrac{157}{2}\) . 5
= 785/2
36 : { 336 : [ 200 - (12 + 8 : 20)]}
= 36: { 336 : [ 200 - 62/5]}
= 36 : { 336 : 938/5)
= 36 : 120/67
= 201/10
55 - [ 49 - ( 23 .17 -23 .14)]
= 55 - [ 49 -23 ( 17-14)]
= 55 - [ 49 - 8.3}
= 55 - [ 49 - 24]
= 55 - 25
= 30
{132 - [ 115 - ( 16- 8) ] : 2} .5
= {132 -[ 115 - 8] :2} .5
= {132 - 107:2} .5
= \dfrac{157}{2}2157 . 5
= 785/2
36 : { 336 : [ 200 - (12 + 8 : 20)]}
= 36: { 336 : [ 200 - 62/5]}
= 36 : { 336 : 938/5)
= 36 : 120/67
= 201/10
55 - [ 49 - ( 23 .17 -23 .14)]
= 55 - [ 49 -23 ( 17-14)]
= 55 - [ 49 - 8.3}
= 55 - [ 49 - 24]
= 55 - 25
= 30
![](https://rs.olm.vn/images/avt/0.png?1311)
`3,5 : (x+1)-5,7=1,3`
`3,5 : (x+1)=1,3+5,7`
`3,5 : (x+1)=7`
`x+1=3,5:7`
`x+1=0,5`
`x=0,5-1`
`x=-0,5`
Vậy `x=-0,5`
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
4/9 x X + 14/9 x X = 13,2 : 0,01
= 4/9 x X + 14/9 x X = 1320
= X . ( 4/9 + 14/9) = 1320
= X . 2 = 1320
= X = 1320 : 2
= X = 660
4/9 x X + 14/9 x X = 13,2 : 0,01
= 4/9 x X + 14/9 x X = 1320
= X . ( 4/9 + 14/9) = 1320
= X . 2 = 1320
= X = 1320 : 2
= X = 660